Field survey of foliage-dwelling spiders (Arachnida, Araneae) in Peninsular Malaysia - Dzulhelmi Muhammad Nasir; Suriyanti Su; Badiozaman Sulaiman; Madihah Halim; Nur-Syahirah Mamat; Farah Nadiah Rosli; Faszly Rahim (Jurnal Entomologi Indonesia, 2019)
Diversity of spider groups have received less research attention and there are limited published references for spiders from Peninsular Malaysia. The current survey was conducted to locate and identify foliage-dwelling spiders (Arachnida, Araneae) at five different sites in Peninsular Malaysia. Spider specimens were collected using manual search and sweep-netting between September 2012 and November 2012. A total of 92 morpho-species from 65 genera that belong to 15 families have been successfully recorded and identified. The greatest proportion of specimens captured (40%) were Foliage-runners (Clubionidae, Miturgidae, Oxyopidae, Pisauridae, Salticidae, Scytodidae, Thomisidae), followed by orb-weavers (Araniedae, Nephilidae, Tetragnathidae, Uloboridae) (36.5%), space-weavers (Pholcidae, Psechridae Theridiidae) (21.5%) and ground-dwellers (Sparassidae) (2.0%). Cluster analysis has revealed that the same habitat types share a more similar diversity composition compared to different habitat types, which indicates that spider assemblage composition was partly co-dependent on vegetation structure. However, no significant difference in spider assemblage composition was found between all the five sites which follows that these diurnal group of spiders are actually adaptable to various habitat types.